Bridging Faith and Therapy: A Systematic Review of Islamic Psychotherapy in Mental Health and Rehabilitation - Haramain, Muhammad; Afiah, Nur (Indonesian Journal of Islamic Counseling, 2024)
The integration of Islamic psychotherapy into contemporary mental health and rehabilitation frameworks has gained increased scholarly attention in recent years. This study presents a systematic literature review of peer-reviewed articles published between 2010 and 2025, focusing on the application, effectiveness, and theoretical foundations of Islamic psychotherapy in diverse settings. Utilizing the PRISMA 2020 protocol, 45 articles were selected from databases such as Scopus, Web of Science, PubMed, and Garuda. Thematic analysis revealed three major trends: the implementation of Islamic psychotherapy within faith-based institutions, the theoretical integration of Islamic principles with Western psychotherapeutic models such as CBT, and outcome-based empirical evaluations. Despite promising findings, the review identified significant gaps in scalability, methodological rigor, and digital adaptation. Few studies explored applications in public institutions or the potential of mobile and teletherapy platforms. The findings underscore the need for a more inclusive, interdisciplinary approach that bridges spiritual values and scientific practice. This study contributes to the development of culturally sensitive mental health strategies and calls for greater integration of Islamic psychotherapy into mainstream psychological services, supported by empirical validation, professional training, and digital innovation